PENGENDALIAN SEDIMEN DALAM BENDUNGAN DENGAN PIPA HISAP TERAPUNG - Pingit Broto Atmadi (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2006)
Abstract Sedimentation represent big threat to continuity a barrage building. Barrage function as reservoir will decrease in line with decreasing volume  at the same time with effect of existence of sedimentation. There is two kinds of way of to overcome the problem of sediment  barrage, that is with operation entry of sediment to reservoir area by removing sediment from barrage. Till in this time handling of[is problem of sediment not yet produced fruit satisfying result. Considering is important of function  from barrage hence needing the effort by is assorted  way of, one of them  cleaning with systems usage of pipe suck adrift, this cleaning is relied on gravitation stream theory as well as calculation charge current in pipe capable to lift sediment which have tuanged barrage base. Item turbulensi theory sediment lifting at open channel stream, item will be upraised if stream turbulensi can generate style box exceeding sediment item gravity  Key words : Pipe suck adrift, Sedimentation.